Influences of a Luck Game on Offers in Ultimatum and Dictator Games: Is There a Mediation of Emotions? - Matarazzo, Olimpia; Pizzini, Barbara; Greco, Claudia (Frontiers in Psychology, 2020)
The ultimatum (UG) and dictator (DG) games are two tasks where a sum of money has to be divided between two players: a proposer and a receiver. Following the rational choice theory, proposers should offer the minimum in the UG and nothing in the DG. The fact that people generally make non-negligible offers in both games has generated extensive research to examine exogenous and endogenous factors underlying such decisions. Among the contextual factors affecting the proposers’ offers, the sense of being entitled to have more, deriving from the manipulated results of skill tasks performed before the UG or DG, has been shown to reduce offers significantly. In this study, we investigate whether manipulating the outcome of a luck game, which does not require any personal ability, influences offers in the UG and DG in ways depending on the game. Moreover, we investigate whether this putative effect is mediated by the changes in emotions elicited by the luck game and/or by the emotions and beliefs related to decision-making. We used a non-economic version of the games, in which tokens were divided instead of money. In the study, 300 unpaid undergraduates (M=152) from different degree programs, aged between 18 and 42 years, participated. The results revealed that the effect of outcome manipulation on offers was moderated by the specific structure of the UG and DG. Instead, emotional reactions barely mediated the effect of the experimental manipulation, suggesting that their role in those decisions is less relevant than is assumed in the literature.